Akun Fufufafa dalam Video Youtube Abraham Samad SPEAK UP (Analisis Wacana Kritis Teun Van Dijk) - Sueb Sueb; Suprihatien Suprihatien (Balai Bahasa Provinsi Bali, 2025)
The viral phenomenon of the fufufafa account that has been discussed by the public has led to various interpretations in the digital space. This research aims to describe how the fufufafa account discourse in the Abraham Samad SPEAK UP talk show program on YouTube. This research uses a descriptive qualitative approach with data sources in the form of videos from the Abraham Samad SPEAK UP YouTube channel that discuss the topic of the fufufafa account. Data was collected through observation and documentation techniques, then analyzed using the critical discourse analysis approach of Teun A. Van Dijks model, which includes three main dimensions of text analysis, social cognition, and social analysis. The results showed that in the text analysis dimension, the discourse is built through macro structure (theme), superstructure (schematic), and micro structure which includes syntactic, semantic, stylistic, and rhetorical elements. In the social cognition dimension, schemas such as person schema, self schema, role schema, and event schema are found that shape the speakers' perspective on issues. Meanwhile, in the social analysis, there are power relations and control over access to information that influence the framing of discourse. These findings show how digital media shapes the construction of meaning through language. AbstrakFenomena viralnya akun fufufafa yang ramai diperbincangkan publik telah menimbulkan beragam penafsiran di ruang digital. Penelitian ini bertujuan untuk mendeskripsikan wacana akun fufufafa dalam program talkshow Abraham Samad SPEAK UP di YouTube. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan sumber data berupa video dari kanal YouTube Abraham Samad SPEAK UP yang membahas topik akun fufufafa. Data dikumpulkan melalui teknik observasi dan dokumentasi, kemudian dianalisis dengan pendekatan analisis wacana kritis model Teun A. Van Dijk, yang mencakup tiga dimensi utama analisis teks, kognisi sosial, dan analisis sosial. Hasil penelitian menunjukkan bahwa pada dimensi analisis teks, wacana dibangun melalui struktur makro (tema), superstruktur (skematik), dan struktur mikro yang mencakup unsur sintaksis, semantik, stilistik, dan retoris. Kemudian pada dimensi kognisi sosial, ditemukan skema-skema seperti skema person, skema diri, skema peran, dan skema peristiwa yang membentuk cara pandang narasumber terhadap isu. Sementara itu, pada analisis sosial, terlihat adanya relasi kuasa dan kendali akses terhadap informasi yang turut memengaruhi pembingkaian wacana. Temuan ini memperlihatkan bagaimana media digital membentuk konstruksi makna melalui bahasa.